Drawing into being: The trap as a diagram for ecological exchange between art and anthropology - Spriggs, Hermione (Journal of material culture, 2019)
This article aims to further Alfred Gell's assertion (Vogel's net: Traps as artworks and artworks as traps', Journal of Material Culture, 1996) that traps be considered as functional artworks and vice versa, and builds on this foundation for an even bolder approach to practical exchange between art and anthropology. The trap is explored as a particular kind of technology that enables analytical play between species perspectives and disciplines which might at first appear to be ontologically distinct from one another, but are in fact recursively shaped and shape one another. Particular emphasis is placed on the craftiness' of animal traps as adaptable structures with a playful (if combative) propensity, by way of parallel examples of artistic forms and engagements that are tricky' in relation to existing norms of consumption and production - or even in regards to the label of Art itself., Gell's initial comparison is used as a means by which traps and artworks might bear more integrally upon one another to suggest not only certain structural similarities (as Gell suggested), but further co-generative potential for new frames of anthropological engagement and more-than-human artistic production. The trap emerges as a diagram of practice' that enables visual art to locate itself in an ecologically recursive relationship with a given environment. Just as Gell suggested, the trap takes art beyond existing art-historical frameworks and aesthetic conventions. As a method for anthropology, trapping suggests an experimental approach to fieldwork that adopts unconventional media from a given context to playfully draw from its more-than-human object of study. It is for both art and anthropology alike to conjure up the question - like a well-set trap - what is it like to be' and draw into being that which one is not?